Module and Lesson Unit Templates in the Course Book English in Mind: A Content Analysis - Krisdian, Joseph Emmanuel; Mukarto, Fransiscus Xaverius; Yuniarto, Laurensius Albertus Chandra (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2022)
Using coursebooks in language learning is a crucial means of obtaining knowledge. This study focused on Indonesia, delves into examining the first edition of Cambridge University Press's English in Mind: Student's Starter Book through content analysis. The research objective is to uncover the book's module and lesson unit templates. The analysis concentrates on two of the four modules and their accompanying lesson units. Findings indicate that the module template is consistent and includes three significant components: topics and learning outcomes, lesson units, and assessment. The template for lesson units, however, displays a certain degree of variability regarding the number of sections and the content of learning tasks. This variance arises from the necessary scaffolding processes to achieve the unit's intended learning outcomes. Examining coursebook content through content analysis is crucial in understanding the language learning process and determining the effectiveness of instructional materials. In conclusion, the results of this study contribute to the advancement of language education by highlighting the significance of coursebook analysis in evaluating the quality and consistency of language instructional materials.